Use of oxytocin to improve diagnosis of subclinical mastitis caused by Staphylococcus aureus - Jonsson, Lina (SLU/Dept. of Animal Nutrition and Management (until 231231), 2014)
Mastitis, inflammation in the udder tissue, caused by S. aureus is a big problem in dairy cattle production. It causes suffering for the cow and curing or replacing the infected cow is costly for the farmer. It is known that beef cattle also suffer from mastitis caused by S. aureus. The aseptical methods commonly used to diagnose mastitis in most cases require several milk samples from the same udder quarter. A method where only one sample is necessary would be useful, especially in beef cattle production where handling and milking the animal is difficult. Research has shown that S. aureus can change shape into microabscesses, entering the inside of the secretory cell. In this shape it is hidden from the immune system. A high dose of oxytocin could break the secretory cell wall, were the microabscesses are hidden, to shed them in to the milk. The objective of this study was to evaluate if the milk ejecting hormone oxytocin could be used to detect subclinical mastitis caused by Staphylococcus aureus (S. aureus). In this trial 14 cows of the breed Swedish red and white were used. Ten produced milk with a somatic cell count (SCC) higher than 250 000 cells per ml milk (HSCC). A control group of four cows producing milk with a SCC lower than 50 000 cells per ml milk (LSCC) were also included. During the trial milkings samples were taken aseptically for bacteriological examination of premilk and postmilk. Premilk samples were taken for SCC analysis. Also composite milk samples for analysis of SCC and composition of fat, protein and lactose were taken during the milking. During the trial the cows were each given a single intramuscular injection with 100 international units of oxytocin. It was found that the oxytocin injection (OI) resulted in a higher (p<0.0001) amount of milk fat in the milking that followed direct after the injection, compared with all of the other milkings. The OI is known for increasing the amount of residual milk, which has a higher percent of fat. The third milking after the OI, the percent of fat was decreased (p<0.01) compared with all of the other milkings. The amount of protein was higher (p<0.001) at second milking after the OI. At this milking all the cows had a higher (p<0.0001) SCC value and a lower (p<0.0001) percent of lactose. The OI opens up the gap in the tight junctions, which separates the blood from the milk, more somatic cells from the blood can therefore enter the milk and the lactose can move in to the blood. The HSCC cows had a higher amount of somatic cells than the LSCC group throughout the whole trial period. The two groups both had a SCC peak at the second milking after the OI. Looking at the HSCC cow’s udders it was revealed that almost all of the extreme SCC values after the OI came from an udder quarter that had a bacterial infection. There is no result from the bacterial samples that gives support to the theory that a high dose of oxytocin would shed out S. aureus that would not be shedded out otherwise. In order to really evaluate the theory behind this trial it would be necessary to look at larger number of cows and also collect aseptic milk samples before the trial starts to be able to select cows with a high SCC that does not have any detected udder pathogen.